If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5z + -14 = 8z + 4 Reorder the terms: -14 + 5z = 8z + 4 Reorder the terms: -14 + 5z = 4 + 8z Solving -14 + 5z = 4 + 8z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-8z' to each side of the equation. -14 + 5z + -8z = 4 + 8z + -8z Combine like terms: 5z + -8z = -3z -14 + -3z = 4 + 8z + -8z Combine like terms: 8z + -8z = 0 -14 + -3z = 4 + 0 -14 + -3z = 4 Add '14' to each side of the equation. -14 + 14 + -3z = 4 + 14 Combine like terms: -14 + 14 = 0 0 + -3z = 4 + 14 -3z = 4 + 14 Combine like terms: 4 + 14 = 18 -3z = 18 Divide each side by '-3'. z = -6 Simplifying z = -6
| -n+7=n-9 | | x+x(2)+x+86=180 | | -2(6x-4)=8-12*x | | -6d=-8 | | 6-3x+2x^2-x^3=0 | | -x=7x+2 | | 4*x+19=-9-6x | | x+5=7x+2 | | 25-(-5)-7= | | 3x-22+65=180 | | 5=18a | | 3+x-4=7x-2 | | 2u^2+3u-20=0 | | 4*x+3=2(2x+9) | | (x-8)=x-3 | | 6+2(2-4x)=6x+2(2x-4) | | 30+40x=35 | | 55=285-10e | | 2(6x+10y)+8=0 | | 4(x-6)-10=2x | | b=11-a | | 2(x-4)-6=-6(-2x+4)-6x | | 6r+5=55 | | k+3=6+k | | 30+(.0825*30)+(15%*30)= | | 6(y+2)=-2(8y-7)+6y | | -26+26=-15p-10p | | 11x-4=5x+9 | | x*12=-2 | | X+3(4)=48 | | 3x+10=3x+4+1 | | 2(x-1)-3x=8 |